1994
DOI: 10.2134/agronj1994.00021962008600060011x
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Plant Water Evaporation from Strip‐Tilled Cotton: Measurement and Simulation

Abstract: It is estimated that 20% of cotton producers in the Texas High Plains use the strip tillage practice of planting cotton (Gossypium hirsutum L.) in residues of chemically terminated winter wheat (Triticum aestivum L.). The effect of the residue on water use partitioning between soil (Es) and crop (Ec) evaporation has not been reported. This study tested the hypothesis that the cumulative evapotranspiration (Et), of crop ina strip tillage system and in conventional tillage are similar, and that the residue modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 0 publications
1
64
2
2
Order By: Relevance
“…Dessa forma, alguns estudos indicam que plantas de algodão cultivadas sob sistema de plantio direto apresentam maior eficiência no uso da água do solo e maior taxa de transpiração, se comparadas às cultivadas em sistema convencional de preparo do solo (Lascano et al, 1994). Essa maior taxa transpiratória pode causar grande resfriamento das folhas por evaporação, possibilitando a diminuição da temperatura do dossel (Pettigrew & Jones, 2001).…”
Section: Resultsunclassified
“…Dessa forma, alguns estudos indicam que plantas de algodão cultivadas sob sistema de plantio direto apresentam maior eficiência no uso da água do solo e maior taxa de transpiração, se comparadas às cultivadas em sistema convencional de preparo do solo (Lascano et al, 1994). Essa maior taxa transpiratória pode causar grande resfriamento das folhas por evaporação, possibilitando a diminuição da temperatura do dossel (Pettigrew & Jones, 2001).…”
Section: Resultsunclassified
“…Other E and T Partitioning Lascano et al (1994) reported a 100-day E reduction of 39% for a stubble/no-till treatment verses a conventional tillage treatment for cotton on an Olton sandy clay loam soil in Lubbock, Tex. (Table 10).…”
Section: Evaporation Based On Methods Of Water Applicationmentioning
confidence: 99%
“…In 1982, there were 56 mm of light rain, and in 1984 there were 70 mm of heavier rain (Table 9). Lascano et al (1994) reported the cumulative lOa-day soil evaporation for the two treatments. These treatments were con ventional tillage and stubble/no-till (NT) treatments for cotton on an Olton sandy clay loam soil in Lubbock, Tex.…”
Section: Microlysimetersmentioning
confidence: 99%
“…In our studies, coupling notillage with high-residue preservation practices could reduce soil water evaporative losses during the summer season by about 4 inches (10.2 centimeters), or 13%, assuming a seasonal evapotranspiration demand of 30 inches. In Texas, a study of strip-till cotton grown in wheat residues, compared to cotton under conventional tillage, showed decreased soil water evaporation, increased crop transpiration and an increase in water use efficiency of 37% (Lascano et al 1994). …”
Section: Prospects For Californiamentioning
confidence: 99%